Composite material and preparation method thereof, battery pole piece, battery and electric device
By coating the surface of the electrode active material with conductive agent and non-fibrillated adhesive, a conductive mesh structure is formed, and the complexity and cost of fibrillation treatment in the preparation of dry battery electrode sheets is solved, and a stable, low-cost and environmentally friendly battery electrode sheet preparation is achieved.
Patent Information
- Application Number
- CN202311394177.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
In the dry preparation of battery pole sheets, the prior art requires fibrillation treatment of adhesives, resulting in complex processes, high cost and unfriendly to the environment.
By coating the surface of the electrode active material with conductive agent and non-fibrillated adhesive, a coating layer with both bonding and conductive properties is formed, which is directly used for the preparation of dry battery electrode sheets.
It realizes the stable preparation of dry cell poles without fibrillation, simplifies process steps, reduces costs, and is environmentally friendly, suitable for industrial scale production.
Smart Images

Figure CN119890246A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery materials, and specifically relates to a composite material and a preparation method thereof, a battery pole piece, a battery and an electrical device. Background Art
[0002] New energy vehicles have developed rapidly in recent years. The battery drive system is the main factor affecting the performance and cost of new energy vehicles. Secondary batteries have become the preferred power supply in the current new energy vehicle battery drive system due to their high energy density, low memory effect and high operating voltage.
[0003] The preparation of battery poles for secondary batteries generally adopts the solvent method, that is, the active material, conductive agent and binder are first prepared into a slurry, and then the slurry is coated on the current collector and dried to form a film. The solvent method for preparing battery poles generally involves toxic and expensive organic solvents, and the evaporation and recovery of the solvent will also cause certain energy consumption. The solvent-free dry process for preparing battery poles has the characteristics of low energy consumption and environmental friendliness. However, when preparing battery poles by the dry process, the binder exists in a fiberized form, and the fibrillation of the binder is a key step. Because the fibrillation process of the binder is complex and the conditions are harsh, the cost of using the binder for dry electrodes increases. Summary of the invention
[0004] In view of the above problems, the present application provides a composite material and a preparation method thereof, a battery electrode, a battery and an electrical device, aiming to solve the technical problem of how to simply and low-costly prepare electrodes by dry method.
[0005] In a first aspect, an embodiment of the present application provides a composite material, comprising a core and a coating layer coated on at least a portion of the surface of the core, wherein the core comprises an electrode active material, and the coating layer comprises a conductive agent and a non-fibrillated binder.
[0006] The embodiment of the present application uses a conductive agent and a non-fibrillated binder to coat the surface of the electrode active material. The conductive agent fully wraps the electrode active material and has a good bonding effect. Such a composite material has a stable structure and can be used alone as a film-forming powder for dry-process battery pole pieces, and the powder is not easy to fall off. At the same time, based on the use of a non-fibrillated binder in the coating layer, the dry process of using a composite material for battery pole pieces without fibrillated materials is not only simple in steps and reduces costs, but also environmentally friendly, and has a good application in the industrial-scale production of battery pole pieces.
[0007] In some embodiments, the conductive agent and the non-fibrillated binder in the coating layer form a non-continuous network structure.
[0008] The composite material has a coating layer with a special structure, which is beneficial to the transmission of electrolyte and active metal ions when made into battery electrodes. At the same time, the conductive agent and binder in the coating layer are dispersed on the surface of the active material to form a network structure. Pores are formed between the dispersed conductive agent and the binder to expose the surface of the active material. In this way, a composite material can be formed that can be directly used for dry-process electrodes. The powder has good stability and few side reactions during the dry coating process, thereby improving the charge and discharge performance.
[0009] In some embodiments, the coating layer has a thickness of 200 nm to 1200 nm. Optionally, the coating layer has a thickness of 600 nm to 800 nm.
[0010] The coating layer of the composite material has a thickness of 200nm to 1200nm, which can play a good coating role while having both bonding and conductive properties.
[0011] In some embodiments, the electrode active material is a positive electrode active material, the positive electrode active material includes secondary particles, and the particle size D of the positive electrode active material is v D50 is 2 μm to 18 μm. Optionally, D50 is 5 μm to 12 μm.
[0012] The positive electrode active material of the above structure can be coated with a conductive agent and a binder to form a composite material that can be directly used for a dry-process positive electrode plate and is easy to form a film.
[0013] In some embodiments, the electrode active material is a negative electrode active material, the negative electrode active material has a lamellar structure, and the particle size D of the negative electrode active material is v 50 is 2 μm to 18 μm, optionally, D v 50 is 5μm~12μm.
[0014] The negative electrode active material of the above structure can be coated with a conductive agent and a binder to form a composite material that can be directly used for dry-process negative electrode plates and is easy to form a film.
[0015] In some embodiments, the weight ratio of the electrode active material to the conductive agent and the binder is 90-99:0.5-5:0.5-5.
[0016] The conductive agent and the binder in the above-mentioned ratio range in the composite material are coated on the surface of the electrode active material to form a uniform coating layer having both bonding effect and conductive property.
[0017] In some embodiments, the softening temperature of the binder is 60 to 150° C. Optionally, the binder includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, ethylene-vinyl acetate copolymer and polytetrafluoroethylene; and / or,
[0018] The conductive agent includes at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
[0019] The above-mentioned conductive agent and binder can be directly coated on the surface of the electrode active material, and can be directly used as a film-forming powder for dry-process battery pole pieces without fibrillation treatment.
[0020] In a second aspect, an embodiment of the present application provides a method for preparing a composite material, comprising:
[0021] Provide electrode active materials, binders and conductive agents:
[0022] Performing a first mixing process on the electrode active material and the binder to obtain a mixed material;
[0023] The mixed material and the conductive agent are subjected to a second mixing process to obtain a composite material.
[0024] In the embodiment of the present application, the mixing process of controlling the adding order is performed, and the electrode active material and the binder are first mixed. The binder is coated on the surface of the electrode active material to form a bonding network. Then, the mixed material and the conductive agent are mixed for a second time. The conductive agent is intercalated through the bonding network to form a coating layer having both bonding and conductive properties. In this way, a composite material for preparing dry-process battery pole pieces can be directly obtained without fibrillation treatment.
[0025] In some embodiments, the first mixing process includes: stirring and mixing at 0-50° C. for 5-90 min, and then stirring and mixing at 60-150° C. for 5-30 min; and / or,
[0026] The second mixing treatment includes: stirring and mixing at 0-80° C. for 5-90 min.
[0027] The first mixing treatment under the above conditions is pre-mixed at 0-50°C, and then the binder is softened and mixed at 60-150°C, so that the binder can be cast and coated on the surface of the electrode active material to form a bonding network. The second mixing heat treatment under the above conditions can make the conductive agent intercalate through the bonding network to form a coating layer containing the conductive agent and the binder on the surface of the electrode active material.
[0028] In some embodiments, the weight ratio of the electrode active material to the conductive agent and the binder is 90-99:0.5-5:0.5-5.
[0029] When the conductive agent and the binder are coated on the surface of the electrode active material in the above-mentioned ratio, a uniform coating layer having both a binding effect and a conductive property can be formed on the electrode active material.
[0030] In some embodiments, the softening temperature of the binder is 60 to 150° C. Optionally, the binder includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, ethylene-vinyl acetate copolymer and polytetrafluoroethylene; and / or,
[0031] The conductive agent includes at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
[0032] The above-mentioned conductive agent and binder can be directly coated on the surface of the electrode active material, and can be directly used as a film-forming powder for dry-process battery pole pieces without fibrillation treatment.
[0033] In some embodiments, the electrode active material is a positive electrode active material, the positive electrode active material includes secondary particles, and the particle size D of the positive electrode active material is v 50 is 2 μm to 18 μm, optionally, D v 50 is 5μm~12μm.
[0034] The positive electrode active material of the above structure can be coated with a conductive agent and a binder to form a composite material that can be directly used for a dry-process positive electrode plate.
[0035] The electrode active material is the negative electrode active material, which has a lamellar structure and a particle size D v 50 is 2 μm to 18 μm, optionally, D v 50 is 5μm~12μm.
[0036] The negative electrode active material of the above structure can be coated with a conductive agent and a binder to form a composite material that can be directly used for a dry-process negative electrode plate.
[0037] In a third aspect, an embodiment of the present application provides a battery electrode, including a current collector and an electrode active layer combined with the current collector, the electrode active layer containing the composite material of the first aspect of the embodiment of the present application and / or the composite material prepared by the preparation method of the second aspect of the embodiment of the present application.
[0038] The battery pole piece provided in the embodiments of the present application uses the composite material of the first aspect of the embodiments of the present application and / or the composite material prepared by the preparation method of the second aspect of the embodiments of the present application. The conductive agent and the binder in the composite material are coated on the surface of the electrode active material to form a coating layer that has both bonding and conductive properties. Therefore, the battery pole piece of the present application can be directly prepared by a dry process, which is conducive to industrial-scale production.
[0039] In a fourth aspect, the present application provides a method for preparing the battery electrode sheet according to the third aspect, comprising:
[0040] The composite material is dry-coated on the current collector and then hot-pressed to form an electrode active layer.
[0041] The embodiment of the present application utilizes a composite material as a film-forming powder, in which a conductive agent and a binder are coated on the surface of an electrode active material to form a coating layer having both bonding and conductive properties. There is no need for a fibrillation step, and the composite material is directly coated on a current collector by a dry process and hot-pressed to obtain a battery pole piece. Therefore, the preparation method of the battery pole piece of the present application is not only simple in steps and low in cost, but also environmentally friendly and can be produced on an industrial scale.
[0042] In a fifth aspect, an embodiment of the present application provides a battery, the battery comprising the battery pole piece according to the third aspect of the embodiment of the present application and / or the electrode pole piece prepared by the preparation method according to the fourth aspect of the embodiment of the present application.
[0043] The battery of the embodiment of the present application includes the battery pole piece of the third aspect of the embodiment of the present application and / or the electrode pole piece prepared by the preparation method of the fourth aspect of the embodiment of the present application. Therefore, such a battery is easy to mass produce, has low cost, and is environmentally friendly.
[0044] In a sixth aspect, an embodiment of the present application provides an electrical device, the electrical device comprising the battery of the fifth aspect of the embodiment of the present application.
[0045] The electric device provided in the embodiment of the present application includes the battery according to the fifth aspect of the embodiment of the present application. Such an electric device has low preparation cost and is environmentally friendly.
[0046] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0048] Figure 1 is a schematic structural diagram of a composite material according to an embodiment of the present application;
[0049] Figure 2 It is a schematic diagram of the preparation method of the composite material of the embodiment of the present application;
[0050] Figure 3 A schematic diagram of a battery cell structure of an embodiment of a secondary battery of the present application;
[0051] Figure 4 for Figure 3An exploded schematic diagram of the battery cell shown;
[0052] Figure 5 This is a schematic structural diagram of an implementation scheme of a battery module according to an embodiment of the present application;
[0053] Figure 6 This is a schematic structural diagram of an implementation scheme of a battery pack according to an embodiment of the present application;
[0054] Figure 7 for Figure 6 A schematic diagram of the exploded structure of the battery pack shown;
[0055] Figure 8 A schematic diagram of an embodiment of an electrical device including a battery according to an embodiment of the present application as a power source;
[0056] Fig. 9 5000 times scanning electron microscope image of the positive electrode active material NCM811 of Example 1 of the present application;
[0057] Fig.10 10000 times scanning electron microscope image of the composite material of Example 1 of the present application;
[0058] Fig.11 30000 times scanning electron microscope image of the composite material of Example 1 of the present application;
[0059] Fig.12 5000 times scanning electron microscope image of the cross section of the composite material of Example 1 of the present application;
[0060] Fig.13 Appearance diagram of the positive electrode sheet of Example 1 of the present application;
[0061] Fig.14 10000 times scanning electron microscope image of natural graphite, the negative electrode active material of Example 2 of the present application;
[0062] Fig.15 10000 times scanning electron microscope image of the composite material of Example 2 of the present application;
[0063] Fig.16 Appearance diagram of the negative electrode sheet of Example 2 of the present application;
[0064] Fig.17 Appearance diagram of the positive electrode sheet of Comparative Example 1 of the present application;
[0065] Description of reference numerals:
[0066] 11 - inner core; 12 - coating layer; 20 - battery cell; 21 - shell; 22 - top cover assembly; 23 - electrode assembly; 30 - battery module; 40 - battery pack; 41 - upper box; 42 - lower box. DETAILED DESCRIPTION
[0067] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0069] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0070] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0071] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0072] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two), and similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces). "At least one" refers to more than one (including one, two, three, etc.).
[0073] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0074] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0075] With the decreasing traditional energy resources, the development of new energy storage devices has received more and more attention. Among them, secondary batteries have attracted much attention due to their high energy density, high theoretical capacity, good cycle stability and environmental protection characteristics. Secondary batteries can not only be used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but are also widely used in electric vehicles such as electric bicycles, electric motorcycles, and electric vehicles. With the continuous expansion of the application fields of secondary batteries that can be used as power batteries, the market demand is also constantly expanding, and there is an urgent need to reduce the preparation cost of secondary batteries.
[0076] The preparation of battery poles for secondary batteries generally adopts the solvent method, that is, the active material, conductive agent and binder are first prepared into a slurry, and then the slurry is coated on the current collector and dried to form a film. The solvent method for preparing battery poles generally involves toxic and expensive organic solvents, and the evaporation and recovery of the solvent will also cause certain energy consumption. The solvent-free dry process for preparing battery poles has the characteristics of low energy consumption and environmental friendliness, but when the dry process is used to prepare battery poles, the binder exists in a fiberized form. The fibrillation of the binder is a key step, but the fibrillation process is complex and the conditions are harsh, which increases the cost of using the binder.
[0077] Fibrillation generally refers to the process of dry fiberizing raw materials through air flow crushing, jet grinding and other methods. This fiberization process is difficult. The current binders need to be fiberized to achieve dry battery electrode preparation, otherwise the binder powder will easily fall off.
[0078] For example, it has been reported that the electrode active material, conductive agent, and fibrillable binder are premixed and then subjected to an in-situ cross-linking reaction, and then placed in a mixing and dispersing device for a complex homofibrillation process to promote the orderly arrangement of the binder and in-situ fibrillation. The homofibrillation process is cumbersome and has harsh process conditions, which seriously affects the efficiency of large-scale production of battery pole pieces.
[0079] Based on the above considerations, since the preparation of dry-process battery pole pieces requires the use of fibrillated binders, otherwise they are easy to fall off, and the fibrillation step increases the complexity of the process steps, in order to overcome the defect that the current dry process for preparing battery pole pieces requires fibrillation, the embodiment of the present application unexpectedly discovered and designed a powder material for preparing dry-process battery pole pieces without fibrillating the material. Therefore, the following technical solution is proposed.
[0080] Composite material and preparation method thereof
[0081] In a first aspect, the present invention provides a composite material. The composite material has a core-shell structure. In some embodiments, Figure 1 The composite material of the embodiment of the present application includes: a core 11 and a coating layer 12. The core 11 includes an electrode active material, and the coating layer 12 is coated on at least a portion of the surface of the core 11, and the coating layer 12 includes a conductive agent and a non-fibrillated binder.
[0082] The electrode active material in the inner core 11 is an active material used in the battery pole piece. The electrode active material can be a positive electrode active material or a negative electrode active material. If it is a positive electrode active material, the composite material is a positive electrode material, which is used in the positive electrode plate of the battery. The positive electrode active material has active metal ions, and the battery can be charged and discharged by the migration of active metal ions. If the electrode active material is a negative electrode active material, the composite material is a negative electrode material, which is used in the negative electrode plate of the battery. The negative electrode active material has the performance of reversibly de- / embedding the active metal ions of the positive electrode active material. In the composite material of the embodiment of the present application, regardless of whether the inner core 11 is a positive electrode active material or a negative electrode active material, the conductive agent and the non-fibrillated binder can be coated without fibrillation treatment, and can be directly used for the dry preparation of the battery pole piece.
[0083] The coating layer 12 includes a conductive agent and a non-fibrillated binder. The conductive agent provides conductive properties, and the binder provides adhesiveness. The non-fibrillated binder can be understood as a binder that exists in the original particle morphology and has not been fibrillated to form fibers. The conductive agent and the binder are coated on the surface of the inner core 11 to form a coating layer 12, so that the coating layer 12 forms a conductive network with adhesiveness, and the coating layer 12 makes the composite material have a stable core-shell structure, which can be used alone and directly used as a film-forming powder for dry-process battery electrodes.
[0084] In summary, the embodiment of the present application provides a composite material with a stable core-shell structure through the joint action of the core 11 and the coating layer 12. The conductive agent and the non-fibrillated binder are coated on the surface of the electrode active material of the core 11 to form a coating layer 12 that has both bonding and conductive properties. Such a composite material can be used alone as a film-forming powder for dry-process battery pole pieces, and the powder is not prone to falling off. At the same time, based on the use of a non-fibrillated binder in the coating layer 12, the dry process of using a composite material for battery pole pieces that does not require a fibrillated composite material not only simplifies the steps and reduces costs, but is also environmentally friendly and has great application in industrial-scale production of battery pole pieces.
[0085] In some embodiments, the conductive agent and the non-fibrillated binder in the coating layer 12 form a non-continuous network structure.
[0086] The conductive agent and the binder form a discontinuous porous coating layer 12 on the surface of the inner core 11. The binder and the conductive agent in the coating layer 12 have obvious original particle morphology, and there are obvious pores between the particles. The composite material has a coating layer 12 with a special structure, which is beneficial to the transmission of electrolyte and active metal ions after being made into battery electrodes. At the same time, the conductive agent and the binder in the coating layer 12 are mutually dispersed on the surface of the inner core 11 to form a discontinuous network structure. Pores are formed between the conductive agent and the binder to expose the surface of the positive active material of the inner core 1. In this way, a composite material directly used for dry-process electrodes can be formed. The powder has good stability and few side reactions during the dry coating process, thereby improving the charge and discharge performance.
[0087] In some embodiments, the thickness of the coating layer 12 is 200nm to 1200nm. Exemplarily, the thickness of the coating layer 12 can be 200nm, 400nm, 500nm, 600nm, 800nm, 1000nm, 1100nm, 1200nm and other typical but non-limiting thicknesses. The coating layer 12 of the composite material with a thickness of 200nm to 1200nm can not only play a good coating effect on the core 11, but also has good bonding and conductive properties. The composite material with a good coating effect can be used as a powder for the preparation of dry battery pole pieces; at the same time, the composite material with the above-mentioned coating layer 13 thickness can increase the proportion of the electrode active material of the core 11, thereby increasing the gram capacity. Optionally, the coating layer thickness can be 600nm-800nm
[0088] In some embodiments, the weight ratio of the electrode active material to the conductive agent and the binder is 90-99:0.5-5:0.5-5, for example, 94:4:2, 95:3:2, 97:2:1, 98:1.5:0.5, etc., and the specific ratio can be determined according to the actual production line. The conductive agent and the binder in the above-mentioned ratio range in the composite material are coated on the surface of the electrode active material to form a uniform coating layer 12 having both bonding and conductive properties.
[0089] In some embodiments, the softening temperature of the binder is 60 to 150° C. The softening temperature is also called the viscous flow temperature, which is the transition temperature between the high elastic state and the viscous flow state. When processed under this temperature condition, the interaction force between the molecular chains of the binder is destroyed, and relative displacement can occur. From a macroscopic point of view, the binder can flow, thereby forming a bonding network on the surface of the electrode active material without fibrillation.
[0090] Specifically, the binder includes at least one of polyvinylidene fluoride (PVDF), polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), ethylene-vinyl acetate copolymer (EVA) and polytetrafluoroethylene (PTFE); these binders have good bonding properties and do not need to be fibrillated. They can be used in the coating layer 12 of the composite material in the form of original powder to form a bonding coating.
[0091] In some embodiments, the conductive agent includes at least one of conductive carbon black (SP), carbon nanotubes (CNTs) and carbon fibers such as vapor grown carbon fibers (VGCF); these conductive agents have good conductivity and can be intercalated throughout the surface binder to form a uniform conductive network.
[0092] In some embodiments, the binder includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, ethylene-vinyl acetate copolymer and polytetrafluoroethylene, and the conductive agent includes at least one of conductive carbon black, carbon nanotubes and carbon fibers. The combination of the conductive agent and the binder can be directly coated on the surface of the electrode active material and can be directly used as a film-forming powder for dry-process battery pole pieces without fibrillation treatment.
[0093] In some embodiments, when the electrode active material is a positive electrode active material, the positive electrode active material includes secondary particles, and the particle size D of the positive electrode active material is v 50 is 2 μm to 18 μm. For example, the particle size D v 50 may be 2 μm, 4 μm, 5 μm, 10 μm, 12 μm, 14 μm, 18 μm, etc. Typical but non-limiting particle sizes. Particle size D of the positive electrode active material v If the particle size D is too small, film formation is difficult; if the particle size D is too large, subsequent compaction is easily affected. The positive electrode active material with the above particle size structure can be coated with a conductive agent and a binder to form a composite material that can be directly used for dry-process positive electrode sheets and is easy to form a film. v 50 is 5μm~12μm.
[0094] Particle size D v 50 is the volume distribution particle size, D v50 is a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.
[0095] Furthermore, the positive electrode active material may be a positive electrode active material for a battery known in the art, and may be a lithium ion active material or a sodium ion active material. Such a positive electrode active material may be used in a lithium ion secondary battery or a sodium ion secondary battery. Taking lithium ion active materials as an example, the positive electrode active material may include lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), and a ternary material (nickel cobalt manganese oxide NCM or nickel cobalt aluminum oxide NCA). Specifically, taking the ternary material nickel cobalt manganese oxide NCM as an example, it may be Li(Ni x Co y Mn z )O2, where 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, and x+y+z=1.
[0096] In some embodiments, the electrode active material is a negative electrode active material, and the negative electrode active material has a lamellar structure. The lamellar structure of the negative electrode active material can be coated with a conductive agent and a binder to form a composite material that can be directly used for a dry-process negative electrode sheet. At the same time, when preparing a negative electrode sheet, the lamellar structure of the composite material of the negative electrode active material is mostly in surface contact after coating. Hot pressing can make it easier for the binder on the surface of the negative electrode active material to contact and bond the negative electrode active material together to form a film. The particle size D of the negative electrode active material v 50 is 2 μm to 18 μm. For example, the particle size D v 50 may be 2 μm, 4 μm, 5 μm, 10 μm, 12 μm, 14 μm, 18 μm, etc. Typical but non-limiting particle sizes. The particle size D of the negative electrode active material v If the particle size D is too small, film formation is difficult; if the particle size D is too large, subsequent compaction is easily affected. The negative electrode active material with the above particle size structure can be coated with a conductive agent and a binder to form a composite material that can be directly used for dry-process negative electrode sheets and is easy to form a film. v 50 is 5μm~12μm.
[0097] Furthermore, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate.
[0098] In a second aspect, the present invention provides a method for preparing a composite material. Figure 2 As shown, the preparation method of the composite material comprises the following steps:
[0099] S01: Provide electrode active materials, binders and conductive agents:
[0100] S02: performing a first mixing process on the electrode active material and the binder to obtain a mixed material;
[0101] S03: performing a second mixing process on the mixed material and the conductive agent to obtain a composite material.
[0102] The embodiment of the present application controls the mixing process in the order of adding materials. Specifically, the electrode active material and the binder are first mixed for a first time so that the binder is coated on the surface of the electrode active material to form a bonding network. The mixed material and the conductive agent are then mixed for a second time so that the conductive agent is intercalated throughout the bonding network to form a coating layer having both bonding and conductive properties. In this way, the composite material for preparing dry-process battery pole pieces can be directly obtained by the preparation method of the embodiment of the present application without fibrillation treatment.
[0103] In some embodiments, the electrode active material, binder and conductive agent provided in step S01 are all raw materials, and their specific types and proportions have been described in detail above.
[0104] For example, the binder includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, ethylene-vinyl acetate copolymer and polytetrafluoroethylene, and the binder may be a binder that does not require fibrillation treatment. The conductive agent includes at least one of conductive carbon black, carbon nanotubes and carbon fibers. The electrode active material is a positive electrode active material, the positive electrode active material includes secondary particles, and the particle size D of the positive electrode active material is v 50 is 2 μm to 18 μm; taking lithium ion active materials as an example, the positive electrode active materials may include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and ternary materials. Alternatively, the electrode active material is a negative electrode active material, and the negative electrode active material has a lamellar structure and a particle size D v 50 is 5 μm to 12 μm, and the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Further, the weight ratio of the electrode active material to the conductive agent and the binder is 90 to 99: 0.5 to 5: 0.5 to 5.
[0105] Specifically, when the electrode active material is a positive electrode active material, the positive electrode active material, a binder and a conductive agent are subjected to a dry mixing step to obtain a composite material for a positive electrode sheet in an embodiment of the present application; such a composite material can be directly applied to the preparation of a dry positive electrode sheet without fibrillation treatment, for example, by directly preparing a dry positive electrode sheet by dry coating and hot pressing.
[0106] Specifically, when the electrode active material is a negative electrode active material, the negative electrode active material, a binder and a conductive agent are subjected to a dry mixing step to obtain a composite material for a negative electrode sheet in an embodiment of the present application; such a composite material can be directly applied to the preparation of dry-process negative electrode sheets without fibrillation treatment, for example, directly preparing dry-process negative electrode sheets by dry coating and hot pressing.
[0107] In some embodiments, the first mixing process of step S02 includes: stirring and mixing at 0-50°C for 5-90 minutes, and then stirring and mixing at 60-150°C for 5-30 minutes. The electrode active material and the binder are first stirred and mixed at 0-50°C for 5-90 minutes, which is a premixing process. During the premixing process, the electrode active material is not easy to break and is evenly mixed with the binder; then stirring and mixing at 60-150°C for 5-30 minutes. The temperature of this process is appropriately increased relative to the premixing process, which can be greater than or equal to the softening point temperature of the binder and less than the thermal decomposition temperature of the binder. Such a temperature can increase the casting effect of the binder mixing process. By mixing in the above temperature range and time range, the binder can be better and more evenly coated on the surface of the electrode active material to form a bonding network to form a mixed material (intermediate product).
[0108] In some embodiments, the second mixing treatment of step S03 includes: stirring and mixing at 0-80°C for 5-90 minutes. The mixed material and the conductive agent are stirred and mixed at 0-80°C for 5-90 minutes. The conductive agent can be intercalated and penetrated into the bonding network formed by the adhesive after casting, so that the adhesive and conductive agent layers form a conductive network with bonding properties on the surface of the electrode active material. The coating layer formed in this way can play a bonding role and a conductive property at the same time. When preparing the dry battery pole piece in the subsequent preparation, it is coated on the current collector and then hot-pressed to form a film.
[0109] In some embodiments, the preparation method of the composite material of the embodiment of the present application includes: a) fixing the ratio of electrode active material and binder, first mixing at a temperature of 0 to 50°C in a mixer for 5 to 90 minutes without loss to obtain powder A; b) heating the obtained powder A to 60 to 150°C, and mixing at a mixer for 5 to 30 minutes without loss to obtain powder B, which is a mixed material; c) mixing the obtained powder B and the conductive agent at 0 to 80°C in a mixer for 5 to 90 minutes without loss to obtain powder C, which is a composite material. Further, based on the total weight of the composite material of 100%, the weight percentage of the main electrode active material is 90 to 99%, the weight percentage of the binder is 0.5 to 5%, and the mass percentage of the conductive agent is 0.5 to 5%.
[0110] In the above process, the dry powder in the mixer does not require solvent, the mixing equipment is simpler, solvent-free mixing reduces the use of solvents, reduces solvent recovery equipment and electrode drying equipment, saves costs, and thus reduces equipment investment costs; the solvent-free composite material powder coating process does not require solvent volatilization, the heating temperature is reduced, the length of the oven is reduced, and no solvent recovery is required, thereby saving energy consumption, reducing equipment layout, and making the production process more environmentally friendly; more importantly, it does not involve fibrillation treatment of the binder, and the worthy composite material can be directly coated and hot-pressed into a film.
[0111] In some embodiments, a scanning electron microscope method is used to analyze the uniformity of the powder coating of the prepared composite material, and the powder resistivity of the composite material can also be detected by a probe inspection technique, such as a two-probe method or a four-probe method; the probe method can be used to confirm the dispersion uniformity of the composite material by taking the resistivity of the powder tested at different positions, which is simple to operate and highly operable. The resistivity of the composite material powder obtained by mixing in different addition orders is obviously different, while the resistivity of the powder tested at different positions of the composite material prepared by the above preparation method in the embodiment of the present application is very small.
[0112] In some embodiments, the composite powder is tested for resistivity at 8MPa pressure using a two-probe method. For example, when the electrode active material is a different type of positive electrode active material, the measured resistivity of the composite material may be 100-430Ω*cm; when the electrode active material is a different type of negative electrode active material, the measured resistivity of the composite material may be 1-2Ω*cm. Moreover, when the electrode active material is the same positive electrode active material or negative electrode active material, the resistivity at different positions tested varies little and has good uniformity.
[0113] Battery pole piece and preparation method thereof
[0114] In a third aspect, an embodiment of the present application provides a battery electrode, including a current collector and an electrode active layer combined with the current collector, the electrode active layer containing the composite material of the first aspect of the embodiment of the present application and / or the composite material prepared by the preparation method of the second aspect of the embodiment of the present application.
[0115] The battery pole piece provided in the embodiments of the present application uses the composite material of the first aspect of the embodiments of the present application and / or the composite material prepared by the preparation method of the second aspect of the embodiments of the present application. The conductive agent and the binder in the composite material are coated on the surface of the electrode active material to form a coating layer that has both bonding and conductive properties. Therefore, the battery pole piece of the present application can be directly prepared by a dry process, which is conducive to industrial-scale production.
[0116] Specifically, the corresponding positive electrode sheet or negative electrode sheet can be formed by selecting the electrode active material in the composite material.
[0117] In some embodiments, the battery pole piece is a positive pole piece, and the electrode active layer is a positive electrode active layer. Specifically, the positive electrode active layer is obtained by dry film formation of the composite material of the present application. The electrode active material of the composite material is a positive electrode active material.
[0118] Accordingly, the current collector of the positive electrode sheet is also called the positive electrode current collector, and a metal foil or a composite current collector may be used. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0119] In some embodiments, the battery pole piece is a negative pole piece, and the electrode active layer is a negative electrode active layer. Specifically, the negative electrode active layer is obtained by dry film formation of the composite material of the present application. The electrode active material of the composite material is a negative electrode active material.
[0120] Correspondingly, the current collector of the negative electrode sheet is also called the negative electrode current collector, and a metal foil or a composite current collector may be used. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0121] In a fourth aspect, the present application provides a method for preparing the battery electrode sheet according to the third aspect, comprising:
[0122] The composite material is dry-coated on the current collector and then hot-pressed to form an electrode active layer.
[0123] The embodiment of the present application utilizes a composite material as a film-forming powder, in which a conductive agent and a binder are coated on the surface of an electrode active material to form a coating layer having both bonding and conductive properties. There is no need for a fibrillation step, and the composite material is directly coated on a current collector by a dry process and hot-pressed to obtain a battery pole piece. Therefore, the preparation method of the battery pole piece of the present application is not only simple in steps and low in cost, but also environmentally friendly and can be produced on an industrial scale.
[0124] The dry coating in the embodiments of the present application is relative to the wet coating, and thus the dry coating can be understood as not dissolving the composite material in a solvent to prepare a slurry, but directly coating the composite material in a solid form on the surface of the current collector to form a film.
[0125] In some embodiments, the composite material can be dry-coated on the current collector by ultrasonic coating and roller gap coating. For example, the composite material of the embodiment of the present application is ultrasonically unloaded, and a small roller is evenly coated on the current collector, and the battery pole piece obtained by hot pressing, specifically, the hot pressing temperature after dry coating can be 120-160°C; further, after being heated to a certain temperature by an infrared lamp tube, hot pressing is performed by a composite roller to obtain a single-sided dry battery pole piece, and then the other side is coated and hot pressed to obtain a double-sided coated dry electrode pole piece.
[0126] The preparation method of the battery pole piece provided in the embodiment of the present application is that the composite material obtained by dry mixing is directly coated on the surface of the current collector by hot pressing to form a film using a dry method; the production line omits the pulping process, the wet coating and drying process, and the solvent drying and recovery equipment; at the same time, the fibrillation step and equipment are omitted, the investment cost is reduced, the energy consumption is reduced, and the environmental pollution is greatly reduced.
[0127] Battery
[0128] In a fifth aspect, an embodiment of the present application provides a battery, the battery comprising the battery pole piece according to the third aspect of the embodiment of the present application; and / or, the electrode pole piece prepared by the preparation method according to the fourth aspect of the embodiment of the present application.
[0129] The battery of the embodiment of the present application includes the battery pole piece of the third aspect of the embodiment of the present application and / or the electrode pole piece prepared by the preparation method of the fourth aspect of the embodiment of the present application. Therefore, such a battery is easy to mass produce, has low cost, and is environmentally friendly.
[0130] In one embodiment, the battery is a secondary battery, including a lithium ion battery or a sodium ion battery.
[0131] In one embodiment, the secondary battery includes a positive electrode sheet and a negative electrode sheet. When the electrode active material in the composite material of the embodiment of the present application is a positive electrode active material, the electrode sheet of the embodiment of the present application is used as a positive electrode sheet in the secondary battery. When the electrode active material in the composite material of the embodiment of the present application is a negative electrode active material, the electrode sheet of the embodiment of the present application is used as a negative electrode sheet in the secondary battery. Of course, the positive electrode sheet and the negative electrode sheet in the secondary battery can be the battery sheets of the embodiment of the present application at the same time, and they are used separately according to the type of electrode active material.
[0132] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0133] In one embodiment, the isolation film may be made of materials known in the art for battery isolation films. As an example, the isolation film base film may include one or more of polyethylene film, polypropylene film, and polyvinylidene fluoride film.
[0134] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0135] In some embodiments, the electrolyte is an electrolyte. The electrolyte includes an electrolyte salt and a solvent. For a secondary battery that is a lithium ion battery, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorobis(oxalate phosphate) and lithium tetrafluorooxalate phosphate. For a secondary battery that is a sodium ion battery, the corresponding electrolyte salt is replaced with a sodium salt.
[0136] In some embodiments, the solvent in the electrolyte can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0137] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0138] In some embodiments, the secondary battery of the present application may include any one of a battery cell, a battery module, and a battery pack. A battery cell refers to a battery housing and a battery cell encapsulated in the battery housing. There is no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape. Figure 3 The battery cell 20 shown has a square structure.
[0139] In some embodiments, Figure 4 As shown, the outer packaging of the battery cell 20 may include a shell 21 and a top cover assembly 22. The shell 21 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 21 has an opening connected to the receiving cavity, and the top cover assembly 22 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the isolation membrane and the negative electrode sheet contained in the secondary battery of the embodiment of the present application can form an electrode assembly 23 through a winding process and / or a lamination process. The electrode assembly 23 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 23. The number of electrode assemblies 23 contained in the battery cell 20 may be one or more, which can be adjusted according to actual needs.
[0140] The preparation method of the battery cell 20 is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form the battery cell 20. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly 23 through a winding process or a lamination process, and the electrode assembly 23 is placed in an outer package, dried and injected with electrolyte, and then vacuum packaged, left to stand, formed, shaped and other processes are performed to obtain the battery cell 20.
[0141] The battery module is assembled from the battery cells 20 , that is, it may contain a plurality of the battery cells 20 , and the specific number can be adjusted according to the application and capacity of the battery module.
[0142] In some embodiments, Figure 5 FIG. 3 is a schematic diagram of a battery module 30 as an example. Figure 5 As shown, in the battery module 30, the plurality of battery cells 20 may be arranged in sequence along the length direction of the battery module 30. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 20 may be fixed by fasteners.
[0143] Optionally, the battery module 30 may further include a housing having an accommodation space, and the plurality of battery cells 20 may be accommodated in the accommodation space.
[0144] A battery pack is composed of the above-mentioned battery cells 20, that is, it may contain multiple battery cells 20, wherein multiple battery cells 20 may be assembled into the above-mentioned battery module 30. The specific number of battery cells 20 or battery modules 30 contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0145] As in the embodiment, Figure 6 and Figure 74 is a schematic diagram of an exemplary battery pack 40. The battery pack 40 may include a battery box and a plurality of battery modules 30 disposed in the battery box. The battery box includes an upper box body 41 and a lower box body 42, wherein the upper box body 41 is used to cover the lower box body 42 and form a closed space for accommodating the battery modules 30. The plurality of battery modules 30 may be arranged in the battery box in any manner.
[0146] Electrical devices
[0147] In a sixth aspect, an embodiment of the present application provides an electric device, the electric device comprising the battery of the fifth aspect of the embodiment of the present application. The battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device provided by the embodiment of the present application has low preparation cost and is environmentally friendly.
[0148] The electrical device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc. The electrical device may select a secondary battery cell, a battery module or a battery pack according to its use requirements.
[0149] Figure 8 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module can be used.
[0150] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0151] Example
[0152] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0153] Example 1
[0154] A composite material for a positive electrode plate, comprising a core and a coating layer coated on the surface of the core; the core is a positive electrode active material NCM811, D v50 = 8 μm; the coating layer thickness is 900 μm, the coating layer is composed of a binder PVDF and a conductive agent SP, and the binder PVDF is not fibrillated. The weight ratio of the positive electrode active material, the binder and the conductive agent is 94:4:2. The preparation steps of the composite material are as follows:
[0155] a) The positive electrode active material and the binder are mixed in a blender at room temperature (25°C) for 90 minutes without loss to obtain powder A; b) The obtained powder A is heated to 100°C and mixed in a blender for 30 minutes without loss to obtain powder B; c) Powder B and a conductive agent are mixed in a blender at room temperature for 90 minutes without loss to obtain powder C, which is a composite material.
[0156] A method for preparing a positive electrode sheet comprises the following steps:
[0157] The composite material prepared above is evenly coated (i.e., dry coated) on the aluminum foil current collector in solid form directly through an ultrasonic coating device, heated to 150°C by an infrared lamp tube, and then hot-pressed by a composite roller to obtain a single-sided dry electrode sheet, and then the reverse side is coated in the same manner to obtain a positive electrode sheet.
[0158] Example 2
[0159] A composite material for a negative electrode plate, comprising a core and a coating layer coated on the surface of the core; the core is natural graphite, a negative electrode active material, and has a lamellar structure with a Dv50 of 10 μm; the coating layer is 400 μm thick and is composed of a binder PVDF and a conductive agent SP, and the binder PVDF is not fibrillated. The weight ratio of the negative electrode active material, the binder and the conductive agent is 97:2:1. The preparation steps of the composite material are as follows:
[0160] a) The negative electrode active material and the binder are mixed in a blender at room temperature (25°C) for 30 minutes without loss to obtain powder A; b) The obtained powder A is heated to 100°C and mixed in a blender for 15 minutes without loss to obtain powder B; c) Powder B and a conductive agent are mixed in a blender at room temperature for 30 minutes without loss to obtain powder C, which is a composite material.
[0161] A method for preparing a negative electrode sheet comprises the following steps:
[0162] The composite material prepared above is evenly coated (i.e., dry coated) on the copper foil current collector in solid form directly through an ultrasonic coating device, heated to 150°C by an infrared lamp tube, and then hot-pressed by a composite roller to obtain a single-sided dry electrode plate, and then the reverse side is coated in the same manner to obtain a negative electrode plate.
[0163] Example 3
[0164] The difference from Example 1 is that the binder in the composite material is PVP.
[0165] Example 4
[0166] The difference from Example 1 is that the binder in the composite material is EVA.
[0167] Example 5
[0168] The difference from Example 1 is that the binder in the composite material is PTFE.
[0169] Example 6
[0170] The difference from Example 1 is that the positive electrode active material D in the composite material v 50=5μm.
[0171] Example 7
[0172] The difference from Example 1 is that the weight ratio of the positive electrode active material, the binder and the conductive agent in the composite material is 98:1.5:0.5.
[0173] Example 8
[0174] The difference from Example 1 is that in the steps of preparing the composite material, step a) is mixed for 20 minutes, step b) is mixed for 10 minutes, and step c) is mixed for 20 minutes.
[0175] Example 9
[0176] The difference from Example 2 is that the binder in the composite material is PVP.
[0177] Example 10
[0178] The difference from Example 2 is that the binder in the composite material is PVP, and the weight ratio of the negative electrode active material, the binder and the conductive agent is 95:3:2.
[0179] Comparative Example 1
[0180] A method for preparing a composite material, wherein the types and weight ratios of the positive electrode active material, binder and conductive agent raw materials used are the same as those in Example 1, except that:
[0181] a) The positive electrode active material and the conductive agent are mixed in a mixer at room temperature (25°C) for 90 minutes without loss to obtain powder A; b) The obtained powder A is mixed with a binder and mixed in a mixer at room temperature without loss for 90 minutes to obtain powder B; c) Powder B is heated to 100°C and mixed in a mixer without loss for 30 minutes to obtain powder C, which is a composite material. The composite material of this comparative example is difficult to form a film after dry coating and hot pressing.
[0182] Comparative Example 2
[0183] A method for preparing a composite material, wherein the types and weight ratios of the negative electrode active material, binder and conductive agent raw materials used are the same as those in Example 2, except that:
[0184] a) The negative electrode active material and the conductive agent are mixed in a mixer at room temperature (25°C) for 30 minutes without loss to obtain powder A; b) The obtained powder A is mixed with a binder and mixed in a mixer at room temperature without loss for 30 minutes to obtain powder B; c) Powder B is heated to 100°C and mixed in a mixer without loss for 15 minutes to obtain powder C, which is a composite material. The composite material of this comparative example is difficult to form a film after dry coating and hot pressing.
[0185] Performance Testing
[0186] (1) Electron microscope test of composite materials and β-Ray test of battery pole pieces
[0187] β-Ray test principle: β-rays are generated by Kr85 decay. When penetrating the battery pole piece, part of the rays are absorbed, resulting in a certain attenuation of the ray intensity after penetrating the pole piece relative to the incident ray intensity. The attenuation ratio is in a negative exponential relationship with the surface density of the penetrated pole piece. The surface density of the pole piece can be deduced by detecting the ray intensity before and after penetrating the pole piece through an ionization chamber filled with special gas. The pole piece is calibrated by β-Ray, and the weight can be measured directly after calibration.
[0188] Fig. 9 This is the SEM image of the positive electrode active material NCM811 used in Example 1. Figure 10-12 The SEM images of the composite material coated in Example 1 at different magnifications are shown in FIG. Fig. 9 and Figure 10-12 By comparison, it can be seen that: in the embodiment of the present application, the surface of the positive electrode active material is coated with a binder and a conductive agent, the binder obviously does not have fibrillation characteristics, and the binder and the conductive agent are dispersed discontinuously on the surface of the positive electrode active material. From the local figure, it can be seen that the binder and the conductive agent are discontinuously and non-densely coated on the surface of the positive electrode active material, and the particles forming the coating layer have obvious original morphology of the binder and the conductive agent, and there are obvious pores between the particles, and the active material can be exposed.
[0189] Fig.13 This is the appearance of the positive electrode sheet prepared by the dry method in Example 1. From the figure, it can be seen that the composite material is dry-filmed on the surface of the positive current collector, and the composite material does not fall off. Moreover, according to the β-Ray weight measurement data, the single-sided coating weight of the positive electrode sheet composite material is 340±10mg / 1540.25mm 2 , coating weight consistency COV = 0.93%; the weight consistency level is consistent with the wet process level of the production line.
[0190] Fig.14 This is a SEM image of natural graphite, the negative electrode active material used in Example 2. Fig.15 The SEM image of the composite material after coating in Example 2 is shown in FIG. Fig.14 and Fig.15 By comparison, it can be seen that the binder and the conductive agent in the embodiment of the present application are relatively dispersed on the surface of the negative electrode active material, showing a discontinuous dispersed island shape connected to each other into a loose network. This may be related to the larger size of the negative electrode active particles under the scanning microscope. Fig.16 The dry coating results still show good bonding effect.
[0191] Fig.16 This is the appearance of the negative electrode sheet prepared by the dry method in Example 2. From the figure, it can be seen that the composite material is dry-filmed on the surface of the negative electrode current collector, and the composite material does not fall off. Moreover, according to the β-Ray weight measurement data, the single-side coating weight of the negative electrode sheet composite material is 248±15mg / 1540.25mm 2 .
[0192] Fig.17 This is the appearance of the positive electrode sheet of Comparative Example 1. Since the composite material of Comparative Example 1 is difficult to form a film after dry coating and hot pressing, a large area of flaking occurs. The main reason is that the positive electrode active material is first mixed with the conductive agent, and the conductive agent cannot fully wrap the main material. After the binder is added, the binder and the conductive agent are bonded and agglomerated, resulting in the binder being unable to fully play its role during hot pressing.
[0193] (2) Resistivity test of composite materials
[0194] Resistivity is a well-known meaning in the art and can be measured using instruments and methods well-known in the art. The resistivity of the composite material tested in this application refers to the resistance of the internal resistance of the composite material powder volume. The principle is to add two electrode sheets to the composite material powder, and by providing a certain voltage, according to Ohm's law, the powder resistivity is calculated by the ratio of potential to current in the powder compressed by the electrode sheets. For example, the national standard GB / T 30835-2014 "Carbon Composite Lithium Iron Phosphate Positive Electrode Material for Lithium Ion Batteries" can be referred to. At 25°C, 1g of composite material sample is placed in the feeding cup of the resistivity tester, the voltage limit is selected to 5V, and the pressure is slowly and evenly applied to the target pressure of 8Mpa. The resistivity of the powder at different positions is tested by measuring the powder resistivity with a probe.
[0195] The corresponding materials, process parameters and effect data of Examples 1-10 and Comparative Examples 1-2 are shown in Table 1.
[0196] Table 1
[0197]
[0198] In the above Table 1, for the composite material formed by coating the positive active material: in Examples 1 and 2-8, the conductive agent and the non-fibrillated binder are coated on the surface of the positive active material NCM811 to form a composite material with a stable structure, which is directly used as a film-forming powder for the dry-process positive electrode sheet and is not easy to fall off. However, in Comparative Example 1, flaky powder falls off and cannot form a film; for the composite material formed by coating the negative active material: in Examples 2 and 9-10, the conductive agent and the non-fibrillated binder are coated on the surface of the negative active material natural graphite to form a composite material with a stable structure, which is directly used as a film-forming powder for the dry-process negative electrode sheet and is not easy to fall off. However, in Comparative Example 2, flaky powder falls off and cannot form a film. Because the method of first mixing the active material with the conductive agent and then mixing it with the binder in the comparative example cannot form a composite material with a stable coating layer, the obtained powder is prone to flaky powder falling off when used for dry-process electrode preparation. In the present application, the active material is first mixed with the binder and then mixed with the conductive agent so that the conductive agent is intercalated throughout the bonding network to form a structurally stable coating layer, resulting in that Examples 1-10 are better than Comparative Examples 1-2 as a whole, and this solution is applicable and effective to both positive and negative active materials.
[0199] In addition, in Example 4, since the adhesive is replaced by ethylene-vinyl acetate copolymer (EVA), but the process parameters of polyvinylidene fluoride (PVDF) in Example 1 are still used, slight spot-like shedding occurs, but it does not affect the overall use of the dry-process positive electrode sheet. At the same time, by further optimizing and adjusting the process temperature and time parameters of Example 4, the effect of no spot-like shedding can be achieved; in Example 7, slight spot-like shedding occurs due to the small amount of adhesive coating, but it does not affect the overall use of the dry-process positive electrode sheet. This shows that appropriately optimizing the adhesive coating amount can further improve the coating effect.
[0200] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A composite material comprising a core and a coating layer coated on at least a portion of the surface of the core, characterized in that: The inner core includes an electrode active material, and the coating layer includes a conductive agent and a non-fibrillated binder.
2. The composite material according to claim 1, characterized in that The conductive agent and the non-fibrillated binder in the coating layer form a discontinuous network structure.
3. The composite material according to claim 1 or 2, characterized in that: The coating layer has a thickness of 200nm to 1200nm. Optionally, the coating layer has a thickness of 600nm to 800nm.
4. The composite material according to any one of claims 1 to 3, characterized in that The electrode active material is a positive electrode active material, the positive electrode active material includes secondary particles, and the particle size D of the positive electrode active material v D50 is 2 μm to 18 μm, optionally, D50 is 5 μm to 12 μm.
5. The composite material according to any one of claims 1 to 3, characterized in that: The electrode active material is a negative electrode active material, the negative electrode active material has a lamellar structure, and the particle size D of the negative electrode active material v 50 is 2 μm to 18 μm, optionally, D v 50 is 5μm~12μm.
6. The composite material according to any one of claims 1 to 5, characterized in that The weight ratio of the electrode active material to the conductive agent and the binder is 90-99:0.5-5:0.5-5.
7. The composite material according to any one of claims 1 to 6, characterized in that The softening temperature of the binder is 60-150° C. Optionally, the binder includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, ethylene-vinyl acetate copolymer and polytetrafluoroethylene; and / or, The conductive agent includes at least one of conductive carbon black, carbon nanotubes and carbon fibers.
8. A method for preparing a composite material, characterized in that: include: Provide electrode active materials, binders and conductive agents: Performing a first mixing process on the electrode active material and the binder to obtain a mixed material; The mixed material and the conductive agent are subjected to a second mixing process to obtain a composite material.
9. The preparation method according to claim 8, characterized in that: The first mixing process comprises: stirring and mixing at 0-50° C. for 5-90 minutes, and then stirring and mixing at 60-150° C. for 5-30 minutes; and / or, The second mixing treatment includes: stirring and mixing at 0-80° C. for 5-90 minutes.
10. The preparation method according to claim 8 or 9, characterized in that: The weight ratio of the electrode active material to the conductive agent and the binder is 90-99:0.5-5:0.5-5.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The softening temperature of the binder is 60-150° C. Optionally, the binder includes at least one of polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene oxide, ethylene-vinyl acetate copolymer and polytetrafluoroethylene; and / or, The conductive agent includes at least one of conductive carbon black, carbon nanotubes and carbon fibers.
12. The preparation method according to any one of claims 8 to 11, characterized in that: The electrode active material is a positive electrode active material, the positive electrode active material includes secondary particles, and the particle size D of the positive electrode active material v 50 is 2 μm to 18 μm, optionally, D v 50 is 5μm~12μm.
13. The preparation method according to any one of claims 8 to 11, characterized in that: The electrode active material is a negative electrode active material, the negative electrode active material has a lamellar structure, and the particle size D of the negative electrode active material v 50 is 2 μm to 18 μm, optionally, D v 50 is 5μm~12μm.
14. A battery pole piece, comprising a current collector and an electrode active layer combined with the current collector, characterized in that: The electrode active layer contains the composite material according to any one of claims 1 to 7 and / or the composite material prepared by the preparation method according to any one of claims 8 to 13.
15. The method for preparing a battery pole piece according to claim 14, characterized in that: include: The composite material is dry-coated on the current collector and then hot-pressed to form the electrode active layer.
16. A battery, characterized in that: The battery comprises the battery pole piece according to claim 14 and / or comprises the electrode pole piece prepared by the preparation method according to claim 15.
17. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 16.
Citation Information
Cited By
Battery monomer and preparation method thereof, battery device and power utilization device
CN121601664A